PENGGELAPAN PAJAK TINJAUAN MORAL PERPAJAKAN (STUDI KASUS KANTOR PELAYANAN PAJAK PRATAMA MAKASSAR SELATAN) - Nur Indah Pujiati; Syamsu Alam; Amiruddin Amiruddin (Jurnal Riset Perpajakan: Amnesty, 2021)
This study aims to determine the Tax evasion of the Moral Review of Taxation (Study of South Makassar Pratama Tax Office). This research method uses descriptive qualitative research.The results of the study have explained that in knowing how the government can improve tax morale so as to minimize tax evasion at South Makassar KPP is to warn taxpayers about the importance of paying taxes in order to avoid tax sanctions. This is also done in order to improve taxpayer tax morale as seen from the sub-concepts of Pre-Conventional Stages, Conventional Stages, Post-conventional Stages, Attitudes towards Behavior, Subjective Norms, and Behavioral Control. Whereas in discussing the causes of taxpayers to commit tax evasion, it can be seen from financial statement analysis, sales analysis, or contract analysis, then after finding an irregularity in the taxpayer's financial report, an interview can be conducted with the taxpayer to find out the indication of fraud, namely the taxpayer who is has indications of committing fraud based on pressure, opportunity, rationalization, ability, or arrogance.